Gene Inactivation by CRISPR-Cas9 in Nicotiana tabacum BY-2 Suspension Cells - Mercx, Sébastien; Tollet, Jérémie; Magy, Bertrand; Navarre, Catherine; Boutry, Marc (Frontiers in Plant Science, 2016)
Plant suspension cells are interesting hosts for the heterologous production of pharmacological proteins such as antibodies. They have the advantage to facilitate the containment and the application of good manufacturing practices (GMPs). Furthermore, antibodies can be secreted to the extracellular medium, which makes the purification steps much simpler. However, improvements are still to be made regarding the quality and the production yield. For instance, the inactivation of proteases and the humanization of glycosylation are both important targets which require either gene silencing or gene inactivation. To this purpose, CRISPR-Cas9 is a very promising technique which has been used recently in a series of plant species, but not yet in plant suspension cells. Here, we sought to use the CRISPR-Cas9 system for gene inactivation in Nicotiana tabacum BY-2 suspension cells. We transformed a transgenic line expressing a red fluorescent protein (mCherry) with a binary vector containing genes coding for Cas9 and three guide RNAs targeting mCherry restriction sites, as well as a bialaphos-resistant (bar) gene for selection. To demonstrate gene inactivation in the transgenic lines, the mCherry gene was PCR-amplified and analyzed by electrophoresis. Seven out of 20 transformants displayed a shortened fragment, indicating that a deletion occurred between two target sites. We also analyzed the transformants by restriction fragment length polymorphism and observed that the three targeted restriction sites were hit. DNA sequencing of the PCR fragments confirmed either deletion between two target sites or single nucleotide deletion. We therefore conclude that CRISPR-Cas9 can be used in N. tabacum BY2 cells.